The Impact of Self-Monitoring Strategy on Students' Narrative Text Speaking Ability - Ariyani, Rizki Silvia; Ikaningrum, Rini Estiyowati; Arochman, Taufik (Inspiring: English Education Journal, 2024)
The pandemic forced students to study from home, resulting in a lack of direct interaction with teachers. When students returned to school, teachers had to start guiding them from scratch using various teaching strategies. These strategies included discussion and self-monitoring. The purpose of the study was to find out the significant difference of self-monitoring strategies on the students' narrative text speaking ability. A quasi-experimental design was used, with the experimental group receiving the self-monitoring strategy and the control group using discussion strategy. The researchers conducted a study at SMPN 4 Magelang, Central Java. The result of the study showed that there was no significant difference between using self-monitoring strategies and using discussion strategies on students' narrative text speaking ability. However, the self-monitoring strategy had positive effects, such as increasing confidence and reducing fear of speaking in English. The researchers hope others will build on this study to evaluate speaking ability in different academic fields.